Structure analysis of polynomial modules with Pommaret bases - Seiler, Werner M. (Proceedings in applied mathematics and mechanics, 2003)
We show how Pommaret bases of submodules of free polynomial modules can be used to extract structural information like the dimension, the depth or the Castelnuovo-Mumford regularity. In particular, we discuss the syzygy theory of Pommaret bases and its use for the construction of free resolutions.